THE EFFECT OF DOMESTIC INVESTMENT, FOREIGN INVESTMENT AND FOREIGN DEBT ON POVERTY IN INDONESIA - Degrit Nst, Alexander; Mellita Sari, Cut Putri (Journal of Malikussaleh Public Economics, 2024)
This study aims to analyze the effect of domestic investment, foreign investment and foreign debt on poverty in Indonesia in the short term and long term. The data used in this study is a time series obtained from the Indonesian Central Statistics Agency and the World Bank for the period 1990-2022. The data analysis method uses the Vector Error Correction Model. The study results show that domestic investment has a negative and significant effect on poverty in Indonesia in the short term and long term. Foreign investment has a negative and significant effect on poverty in Indonesia in the short term, but in the long term foreign investment has a negative and insignificant effect on poverty in Indonesia. Foreign debt has a positive and significant effect on poverty in Indonesia in the short term and long term.